Factors which Influence the Bleeding Time - den Ottolander, G. J. H; Bleijenberg, A (Thrombosis and Haemostasis, 1962)
A prolonged bleeding time can be due to a vascular, plasmatic, or thrombocytic cause. On the basis of investigations in 8 patients with a prolonged bleeding time, these different forms are discussed.There appeared to be at least two plasmatic factors one of which is the bleeding factor of Nilsson. The demonstration of a thrombocytic cause is sometimes only possible with transfusions of normal platelet suspensions. A patient is described with a prolonged bleeding time due to an acquired thrombo-pathia, resulting from excessive haemorrhages and exchange transfusions.